2022
DOI: 10.3390/ijms232415996
|View full text |Cite
|
Sign up to set email alerts
|

Novel Small Molecule Positive Allosteric Modulator SPAM1 Triggers the Nuclear Translocation of PAC1-R to Exert Neuroprotective Effects through Neuron-Restrictive Silencer Factor

Abstract: The neuropeptide pituitary adenylate cyclase-activating polypeptide (PACAP) exerts effective neuroprotective activity through its specific receptor, PAC1-R. We accidentally discovered that as a positive allosteric modulator (PAM) of PAC1-R, the small-molecule PAM (SPAM1) has a hydrazide-like structure, but different binding characteristics, from hydrazide for the N-terminal extracellular domain of PAC1-R (PAC1-R-EC1). SPAM1 had a significant neuroprotective effect against oxidative stress, both in a cell model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Proteome sequencing confirmed that these proteins, which have been validated to be associated with PACAP and play neuroprotective and nerve-regenerative roles in the nervous system, also exhibit increased expression following treatment with SPAM1. Since our previous report confirmed that SPAM1 can re-set the PACAP-PAC1R system by up-regulating the expression of both PACAP and PAC1-R [9], the results of our multi-omic study not only demonstrate the positive activities of SPAM1 in the nervous system, such as neuroprotection and nerve regeneration, but also help to confirm the positive regulating effect of SPAM1 on re-setting the PACAP-PAC1R system. Several corresponding signal pathways were also revealed by our multi-omic analysis, including the neurotrophin signaling pathway (which is consistent with our SPAM1 data in RGC-5 cells [9]), circadian entrainment, olfactory transduction, and GnRH signaling, which is regulated by PACAP [51].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Proteome sequencing confirmed that these proteins, which have been validated to be associated with PACAP and play neuroprotective and nerve-regenerative roles in the nervous system, also exhibit increased expression following treatment with SPAM1. Since our previous report confirmed that SPAM1 can re-set the PACAP-PAC1R system by up-regulating the expression of both PACAP and PAC1-R [9], the results of our multi-omic study not only demonstrate the positive activities of SPAM1 in the nervous system, such as neuroprotection and nerve regeneration, but also help to confirm the positive regulating effect of SPAM1 on re-setting the PACAP-PAC1R system. Several corresponding signal pathways were also revealed by our multi-omic analysis, including the neurotrophin signaling pathway (which is consistent with our SPAM1 data in RGC-5 cells [9]), circadian entrainment, olfactory transduction, and GnRH signaling, which is regulated by PACAP [51].…”
Section: Discussionsupporting
confidence: 77%
“…GPCRs can regulate gene transcription through an unconventional mode of signal transduction, whereby the GPCR cleaves and relies on its carboxyl-terminal structural domain to translocate to the nucleus [20]. In a previous study, we demonstrated that PAC1-R also has such a transduction pattern [9,21,22]. PAC1-R has a high affinity for PACAP due to a specific region of its N-terminal extracellular domain 1 (EC1) [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations